DIGITAL STORYTELLING UNTUK KEMAMPUAN BAHASA ANAK - Novia Solichah; Rifa Hidayah (Universitas Islam Indonesia, 2022)
Language ability is one of the basic skills that must be trained from pre-school age. The purpose of this study was to examine the effectiveness of the digital storytelling method to improve early childhood language skills. This study used a quasi-experimental design, pretest-posttest nonequivalent control group design. The subjects of this study were 30 students of RAMNU Citra Kartini which were divided into a control group and an experimental group. Measurement of language skills is done by means of a checklist of early childhood language skills. The results of the study were analyzed using the paired sample t-test technique with a Sig value. 0.000 (<0.05) and 0.092 (>0.05) respectively in the control and experimental groups with a large effect size value of 1.623, so the digital storytelling method is very effective for improving early childhood language skills and can be applied in learning early childhood language.